Speech Acts in Prabowo Subianto's Interview During the 2024 Qatar Economic Forum - Afrigh Abrar Brahmantya; Jurianto (Institut Agama Islam Negeri Palopo, 2025)
This study examines the use of speech acts by Prabowo Subianto in his interview at the 2024 Qatar Economic Forum and explains how his language reflects Indonesia’s global economic strategy. It focuses on identifying and categorizing the speech acts used by Prabowo, focusing on locutionary, illocutionary, and perlocutionary aspects to understand how his communication influences both domestic and international audiences. The study employs a qualitative approach, analyzing the interview transcript of Prabowo Subianto using Searle’s theory of speech acts and Austin’s framework for a deeper interpretation. The results reveal that Prabowo predominantly uses assertive (66%), expressive (14%), and commissive (16%) speech acts, projecting confidence and commitment to Indonesia’s economic growth. While directive acts (4%) were less frequent, they were strategically used to challenge critics and reinforce his legitimacy. The findings highlight the significant role of language in shaping perceptions of a country’s economic vision on the global stage. This study underscores the significance of speech acts in shaping political discourse and offers insights into the strategic deployment of language by political leaders in international forums.